Update on structured pain assessment for the documentation of diagnosis-independent symptoms and signs associated with pain - Grömer, Teja W.; Atasever, André T.; Käfferlein, Wolfgang; Janoschka, Jonas; Moeller, Sebastian; Dohrenbusch, Ralf; Kappis, Bernd; Maihöfner, Christian; Lücke, Caroline; Kornhuber, Johannes; Philipsen, Alexandra; Müller, Helge H.O. (Schmerz, 2019)
Concerning the diagnosis and therapy of pain syndromes, standardized descriptions similar to those used in the examination of psychopathological findings via the system produced by the AMDP (“Arbeitsgemeinschaft für Methodik und Dokumentation in der Psychiatrie”, i. e., the working group establishing standardized methodology and documentation within psychiatry) are still lacking. Therefore, the authors of this article have founded a working group to establish standardized methodology and documentation for symptoms and signs associated with pain, although not at a diagnosis-specific level, in order to promote standardization in the documentation of pain and rating of the symptoms associated with a given set of medical results. This article presents a system for documenting the symptoms and signs associated with pain globally and independently of the diagnosis (Structured Pain Assessment System) with nomenclature that is inspired by the AMDP system. The objective of this working group is to develop documentation for a uniform multidimensional pain assessment (with defined terminology) that serves as a comparable and unified standard in the field.
CRIS-Team Scopus Importer:2019-06-07
Keywords: Assessment of pain; Classification; Diagnostic tool; Pain syndromes; Standardization